1993
DOI: 10.1037/0022-3514.64.5.817
|View full text |Cite
|
Sign up to set email alerts
|

Attachment styles, coping strategies, and posttraumatic psychological distress: The impact of the Gulf War in Israel.

Abstract: This study examines the association between adult attachment style and the way people reacted to the Iraqi missile attack on Israel during the Gulf War. One hundred forty Israeli students were interviewed 2 weeks after the war and classified according to their attachment style (secure, avoidant, or ambivalent) and residence area (dangerous vs. less dangerous). Ambivalent people reported more distress than secure people. Avoidant persons reported higher levels of somatization, hostility, and trauma-related avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
430
4
13

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 507 publications
(496 citation statements)
references
References 34 publications
39
430
4
13
Order By: Relevance
“…Previous research indicates that people with avoidant and anxious attachment rely on less constructive ways of coping than those relied on by secure persons (Mikulincer & Florian, 1995;Mikulincer et al, 1993). Several of the previous studies that linked attachment and coping have used situational coping assessments (e.g., the Ways of Coping Scale; Folkman & Lazarus, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that people with avoidant and anxious attachment rely on less constructive ways of coping than those relied on by secure persons (Mikulincer & Florian, 1995;Mikulincer et al, 1993). Several of the previous studies that linked attachment and coping have used situational coping assessments (e.g., the Ways of Coping Scale; Folkman & Lazarus, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, two recent studies (Hammen et al, 1995;Mikulincer et al, 1993) found that adult attachment styles moderated the impact of major life stressors, but the mechanism by which this process operated was not ascertained. Our model suggests that the activation of dysfunctional attitudes and depletions in self-esteem might mediate such relations.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the evidence is consistent with our model. People higher in anxious-ambivalence are more likely to turn to others for help with regulating their negative feelings, whereas those who are more avoidant distance themselves from others (e.g., Collins & Feeney, 2000;Mikulincer, 1998;Mikulincer, Florian, & Weller, 1993;Mikulincer, Orbach, & Iavnieli, 1998;Ognibene & Collins, 1998;Pietromonaco & Feldman Barrett, in press;Simpson, Rholes, & Nelligan, 1992). Indeed, for people high in attachment anxiety, the experimental activation of attachment security (i.e., via subliminally priming the word "love"), which may evoke a representation of an attachment figure, appears to provide a comforting or soothing effect by reducing the accessibility of terror-related words (Mikulincer, Shaver, & Horesh, this volume).…”
Section: Empirical Foundationsmentioning
confidence: 99%